Incentives and Selection in Promotion Contests: Is It Possible to Kill Two Birds with One Stone?. (2nd May 2014) - Stracke, Rudi; Höchtl, Wolfgang; Kerschbamer, Rudolf; Sunde, Uwe
<x xml:space="preserve">Abstract</x> This paper investigates whether a designer can improve both the incentive provision and the selection performance of a promotion contest by making the competition more (or less) dynamic. A comparison of static (one‐stage) and dynamic (two‐stage) contests reveals that this is not the case. A structural change that improves the performance in one dimension leads to a deterioration in the other dimension. This suggests that modifications of the contest structure are an alternative to strategic handicaps. A key advantage of structural handicaps over participant‐specific ones is that the implementation of the former does not require prior identification of worker types. Copyright © 2014 John Wiley & Sons, Ltd.